Recent Progress in Oxygen Electrocatalysts for Zinc–Air Batteries - Yang, Dongjiang; Zhang, Lijie; Yan, Xuecheng; Yao, Xiangdong (Small methods, 2017)
Zinc–air batteries (ZABs) have attracted extensive attention due to their remarkable high theoretical energy output. They represent one of the most promising future power sources. However, many barriers restrict their application on a large scale. One of the main challenges is the sluggish rates of the oxygen‐reduction reaction (ORR) and oxygen‐evolution reaction (OER), which govern the discharging and charging processes of the battery, respectively. Here, recent advances related to oxygen electrocatalyst materials for ZABs are discussed. Detailed discussions will focus on unifunctional ORR electrocatalysts and bifunctional ORR and OER electrocatalysts. Pt‐based nanomaterials, as the best ORR electrocatalysts, possess the virtue of high activity, but have the disadvantages of high cost, scarcity, and poor stability. Thus, materials based on transition metals (alloys, metal oxides, metal nitrides, and spinel oxides) and metal‐free materials are widely investigated as nonprecious ORR catalysts owing to their promising catalytic activities. As for bifunctional ORR and OER electrocatalysts, the following two categories are introduced: (i) metal‐based materials, including single metal/metal‐oxides‐based materials and mixed‐metal/metal‐oxides‐based materials; and (ii) metal‐free materials. Finally, perspectives on the continuous research and limitation of the current ZAB technology are provided. Zinc–air batteries (ZABs), which generate electricity through a redox reaction between zinc metal and oxygen, have attracted extensive attention. The sluggish rates of the oxygen reduction and evolution reactions, which govern the discharging and charging processes of the battery, respectively, have largely limited their development. A timely snapshot of oxygen electrocatalysts for ZABs is provided.